Argentine medicinal plants with potential antifungal activity - Rubén V. D. Rondina; Arnaldo L. Bandoni; Jorge D. Coussio
The Argentine flora is represented by more than 9000 higher plants, from which about 1600 are used as home remedies. The cited should be assayed for its supposed activity. In the present case, a total of 58 potentially useful antifungal plants has been identified by reviewing the data about their popular use in Argentina. The results were compiled in a table encompassing the mentioned species which are worth to be tested for its antifungal activity. The list contains (a) the binary name of each plant (genus and species), (b) botanical family, (c) indication(s) or use(s) according to the folklore medicine and its interpretation and/or (d) origin of the data.